Development of E-Comic Based on Culturally Responsive Teaching on the Topic of Matter and Its Changes to Improve Students’ Science Literacy - Listiyowati, Siti; Widiyatmoko, Arif; Sumarni, Woro; Rusilowati, Ani; Saptono, Sigit (Journal of Innovative Science Education, 2025)
This study examined the effectiveness of e-comics based on culturally responsive teaching (CRT) in improving students' science literacy. A quasi-experimental design was employed with seventh-grade students at SMP Negeri 3 Lasem in the 2024/2025 academic year as the population. The sample was selected using cluster random sampling, with Class VII C assigned as the control group and Class VII D as the experimental group. Data were collected using a scientific literacy test and analyzed through quantitative and descriptive methods. The findings revealed that e-comics based on CRT significantly improved students' scientific literacy. The experimental group achieved an average N-gain score of 0.64 (moderate category), which was higher than the control group's average of 0.40. A Mann–Whitney test confirmed a significant difference between the two groups (p < 0.05). These results indicate that e-comics grounded in CRT are effective in enhancing junior high school students' scientific literacy.